2021
DOI: 10.1186/s11671-021-03538-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Polarization-Independent Mid-Infrared Electro-Absorption Modulator Integrated in a Chalcogenide Glass Waveguide

Abstract: A polarization-insensitive graphene-based mid-infrared optical modulator is presented that comprised SiO2/ Ge23Sb7S70, in which two graphene layers are embedded with a semiellipse layout to support transverse magnetic (TM) and transverse electric (TE) polarizing modes with identical absorption. The key performance index for the polarization independent modulator is polarization-sensitivity loss (PSL). The waveguide of our device just supports basic TE and TM modes, and the PSL between two modes is of < 0.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Chen et al proposed a polarization-insensitive graphene modulator, which was polarization-independent for the TE and TM modes [33]. Zhou et al reported a polarization-insensitive graphene-based optical modulator integrated in a chalcogenide glass waveguide [34], where the absorption coefficient variation was almost identical in the wavelength range of 2-2.4 μm for the TE and TM modes. However, there is still no report on the polarization-insensitive waveguide for the SC generation.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al proposed a polarization-insensitive graphene modulator, which was polarization-independent for the TE and TM modes [33]. Zhou et al reported a polarization-insensitive graphene-based optical modulator integrated in a chalcogenide glass waveguide [34], where the absorption coefficient variation was almost identical in the wavelength range of 2-2.4 μm for the TE and TM modes. However, there is still no report on the polarization-insensitive waveguide for the SC generation.…”
Section: Introductionmentioning
confidence: 99%